Islamic Fundamentalism as A Signifier of The Sixth Phase of Globalization - Mohammad Hasan Basri (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2011)
This article examines Islamic fundamentalism through a historical perspective on globalization offered by Roland Robertson, the theory of Islamic fundamentalism and its relation to the involvement of youth in Indonesia. In theory, Islamic fundamentalism is divided into two classifications. First is the